2013
DOI: 10.1093/bja/aes320
|View full text |Cite
|
Sign up to set email alerts
|

Failed tracheal intubation in obstetric anaesthesia: 2 yr national case–control study in the UK

Abstract: We received 57 completed reports (100% response). The incidence using a unit-based estimation approach was one in 224 (95% confidence interval 179-281). Univariate analyses showed the index cases to be significantly older, heavier, with higher BMI, with Mallampati score recorded and score >1. Multivariate analyses showed that age, BMI, and a recorded Mallampati score were significant independent predictors of failed tracheal intubation. The classical laryngeal mask airway was the most commonly used rescue airw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 233 publications
(115 citation statements)
references
References 21 publications
5
101
1
4
Order By: Relevance
“…The majority of obstetric difficult and failed intubations occur during emergencies and out of hours [22,23]. Concerns for rapid delivery of the fetus often lead to time pressure, which may result in poor preparation, planning, communication and performance of technical tasks.…”
Section: Classification Of Evidencementioning
confidence: 99%
See 3 more Smart Citations
“…The majority of obstetric difficult and failed intubations occur during emergencies and out of hours [22,23]. Concerns for rapid delivery of the fetus often lead to time pressure, which may result in poor preparation, planning, communication and performance of technical tasks.…”
Section: Classification Of Evidencementioning
confidence: 99%
“…There are a number of common factors that are associated with difficulty in performing all of these airway management tasks (Appendix 1). The assessment should be documented clearly [22,32]. Oral piercings should be removed before any form of anaesthesia as they may cause trauma and bleeding during intubation as well as carrying the added risk of aspiration if pieces detach [33].…”
Section: Classification Of Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…Increasing obesity rates in the decades since the Closed Claims Study have only augmented the risks. A 2012 study from the UK revealed that, among pregnant women undergoing cesarean section, there was a 7 % increase in the incidence of failed intubation for each 1 kg m -2 increase in BMI above normal [4]. The risk of ventilatory depression extends into the postoperative period.…”
Section: Introductionmentioning
confidence: 99%